The Relationship Between Gadget Use and Motor Development in Preschool Children - Fatiha, Amanda Tiara; Br Saragih, Dameria; Ernawati, Ernawati (Ahmar Metastasis Health Journal, 2025)
The rapid development of digital technology has led to the widespread use of gadgets across all age groups, including preschool children. Devices such as smartphones and tablets are commonly used for entertainment and learning purposes. However, excessive and unsupervised gadget use may negatively affect children’s motor development, which is a crucial indicator of growth during early childhood. This study aimed to examine the relationship between gadget use and motor development among preschool children at KB PAUD Kiddy Club, North Jakarta. This study employed a quantitative approach with a cross-sectional design. The sample consisted of 62 preschool children aged 3–6 years, selected using a total sampling technique. Data were collected using a gadget usage questionnaire and the Denver Developmental Screening Test (DDST) II to assess fine and gross motor development. Data analysis was performed using the Chi-square (χ²) test with a significance level of 0.05. The results showed that most preschool children had moderate to high levels of gadget use. Approximately 66.1% of children primarily used YouTube applications, and 87.1% used smartphones as their main device. Statistical analysis revealed a significant association between the level of gadget use and motor development (p < 0.05), indicating that children with high gadget use were more likely to exhibit suspected or delayed fine and gross motor development. These findings highlight the importance of parental supervision and appropriate regulation of gadget use to support optimal motor development in preschool children.